Aspects Regarding Modeling and Simulation of Evolution Organic Aspects of Human Communities: Array - Prună, Cristian-Sorin (Acta Universitatis Danubius. Relationes Internationales, 2020)
The defining landmarks of the paper have in view the identification of scientific premises that would allow, in a systemic perspective, the modeling and simulation of the organic evolution of human communities. The proposed approach aims at establishing some elements (constants, variables, parameters and relationships) characteristic of politically and politically significant components from a politico-strategic point of view, to be used in building a model for their evolution in the context of building the world system. In an effort to organize such a scientific fund, we have tried to achieve as clear and concise boundaries as possible through research methods - induction and deduction, analysis and synthesis of factors relevant to the dynamics of nations and, implicitly, states and subsystems formed during globalization, both from the perspective of political geography and geopolitics, using the following general procedures: description, explanation and forecast / prevision. The scientific approach also aimed at clarifying the differences and existing relationships between political and geopolitical geography, which contribute to the understanding and structuring of the forms of manifestation of socio-political entities. The identified aspects are intended to be premises for building a model of organic evolution of human society, an approach that also involves making the connection with the global strategic system and with the national strategic ones (integrative, extended and sectoral strategies).